THE INFLUENCE OF SEX HORMONES ON DIABETES: COMPARATIVE ANALYSIS OF WOMEN AND MEN - Karolina Maria Dubiel; Monika Białowąs; Weronika Białowąs; Michał Maćkowski; Sandra Balon; Kacper Piotr Urban; Adam Śmietana; Piotr Szwed; Natalia Julia Sojka; Jakub Jan Magnowski (International Journal of Innovative Technologies in Social Science, 2026)
Diabetes is a complex metabolic disorder whose development and complications are influenced not only by genetic, environmental and lifestyle factors, but also by sex hormones. Women and men differ in regulation of glucose metabolism and insulin sensitivity, which leads to specific patterns in diabetes risk and clinical presentation. Among women, estrogen plays a protective metabolic role before menopause, while hormonal fluctuations during the menstrual cycle, pregnancy and menopause significantly affect glycemic control and may increase the risk of diabetes type 2.In men, testosterone deficiency is strongly associated with insulin resistance, obesity and an increased risk of developing type 2 diabetes, while diabetes itself may contribute to reduced testosterone levels and reproductive dysfunction. These hormonal differences also contribute to variations in diabetes complications, cardiovascular risk and treatment responses between sexes. This article presents a review of current literature on the relation between sex hormones and diabetes, highlighting biological mechanisms, clinical implications and the importance of considering sex-specific factors in prevention, diagnosis and management strategies. Understanding these distinctions may support more personalized and effective approaches to diabetes care.Materials and methods: The review was based on an analysis articles published in the PubMed and Google Scholar databases between 2015 and 2025, using the following keywords: sex hormones, diabetes, sex differences, women and men, glucose metabolism, insulin resistance, diabetes risk.Results: The analysis revealed significant sex-specific differences in the association between sex hormones and glucose metabolism. Women demonstrated a stronger protective influence of estrogens, reflected in better glycemic control and lower insulin resistance before menopause, whereas postmenopausal women showed a marked aggravation in metabolic parameters. In men, higher androgen levels are associated with improved insulin sensitivity, while androgen deficiency correlates with increased diabetes risk. Across both sexes, hormonal imbalance was strongly linked with impaired glucose tolerance, higher prevalence of type 2 diabetes and altered insulin secretion.Conclusions: This study highlights the crucial role of sex hormones in modulating glucose metabolism and showing the risk and progression of diabetes in women and men. Estrogens exert a protective effect in women, particulary before menopause, while their decline is associated with worsening metabolic control. In men, androgen levels appear beneficial for insulin sensitivity, whereas androgen deficiency increases metabolic disturbances. Overall, the findings emphasize that hormonal status should be considered an important determinant in diabetes risk assessment, prevention strategies and therapeutic approaches. Incorporating sex-specific hormonal factors into clinical practice may improve early identification, management and outcomes in diabetes.